Effect of rational and emotional framing on highly involved audience in severe crisis situation: an experimental study on MH370 - Dayang Aizza Maisha Abang Ahmad,; Noratikah Mohamad Ashari,; Mus Chairil Samani, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Rational and Emotional framing is an important crisis response strategy (CRS) used by organisations in its effort to minimize damage and reputational threat of a crisis. The framing effect of a message is crucial not only in influencing the audience attitude towards the organization, but also behaviour. Using one of Malaysia’s most high profiled crises MH370 as a crisis scenario, this study examines the effect of framing used by Malaysia Airlines System in its crisis communication effort on Facebook. Facebook is one of the prominent social media platforms used by organizations in time of crisis. Despite its ability to facilitate immediacy and interactivity, the messages that are spread within the dynamic setting of Facebook however could also create contradicting outcome for the organization. This present study seeks to examine the effect of rational and emotional framing from the perspective of Situational Crisis Communication Theory (SCCT). Cognizant to the influencing factor of audience involvement on the effect of framing, this study incorporates Elaboration Likelihood Model (ELM) in examining audience response towards the organization by taking into consideration audience different motivation to message processing. The convergence of SCCT and ELM has made this study significant as it advances the explication of potential crisis communication effects by underscoring the distinct effect held by rational and emotional frames on highly involved audience; especially in regards to a crisis as severe and nationally salient like MH370.